Peran Dinas Koperasi dan Usaha Mikro Kabupaten Malang dalam Pemberdayaan Usaha Kecil dan Menengah (UKM) - Merrisa Ulvasari; Angguliyah Rizqi Amaliyah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in driving economic growth at both local and regional levels, including in Malang Regency. Their presence not only creates new job opportunities but also stimulates the economic activities of local communities. Nevertheless, SME actors still face a number of significant challenges. These include limited capital, incomplete business legality, low managerial capacity, and restricted access to wider markets. Such conditions often hinder SMEs from optimizing their competitiveness. This research aims to examine the implementation of SME empowerment programs carried out by the Cooperative and Micro Business Office in Kepanjen, as well as to identify supporting and inhibiting factors. The study employed a descriptive qualitative approach, with data collected through in-depth interviews and documentation studies. The findings reveal that SME empowerment was implemented through various programs, such as training to enhance skills, continuous business mentoring, facilitation of access to financing through financial institutions, and product promotion via exhibitions and digital platforms. These programs have provided positive impacts by strengthening the capacity and visibility of SMEs in the region. The success of these programs is supported by the strong commitment of the local government, synergy among institutions, and active participation of SME actors. On the other hand, several obstacles remain, such as low digital literacy among entrepreneurs, difficulties in obtaining financing due to legal constraints, and complex bureaucratic processes. The results of this research emphasize that SME empowerment requires adaptive strategies, continuous mentoring, and proper program mapping in accordance with local conditions.